2019
DOI: 10.1002/cbic.201900582
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Substrate Specificity of the SMYD2 Protein Lysine Methyltransferase and Discovery of Novel Non‐Histone Substrates

Abstract: The SMYD2 protein lysine methyltransferase methylates various histone and non‐histone proteins and is overexpressed in several cancers. Using peptide arrays, we investigated the substrate specificity of the enzyme, revealing a recognition of leucine (or weaker phenylalanine) at the −1 peptide site and disfavor of acidic residues at the +1 to +3 sites. Using this motif, novel SMYD2 peptide substrates were identified, leading to the discovery of 32 novel peptide substrates with a validated target site. Among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“… 176 SMYD2 has been shown to methylate H3K36 even if it lacks specificity on the free histones. This protein is a relatively promiscuous enzyme as it is responsible for the methylation of many substrates (at least six non-histone substrates have been reported in cells), 177 the best characterized of which is p53, where it shows a highly selective activity. SMYD2 methylates p53 at K370, a repressing modification to p53-mediated transcriptional regulation, and reduces p53-mediated apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“… 176 SMYD2 has been shown to methylate H3K36 even if it lacks specificity on the free histones. This protein is a relatively promiscuous enzyme as it is responsible for the methylation of many substrates (at least six non-histone substrates have been reported in cells), 177 the best characterized of which is p53, where it shows a highly selective activity. SMYD2 methylates p53 at K370, a repressing modification to p53-mediated transcriptional regulation, and reduces p53-mediated apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…SMYD2 belongs to the SMYD family that is composed of five members (SMYD1-5) ( Weirich et al, 2020 ). Among them, SMYD1 and SMYD2 are the two most studied isoforms ( Rueda-Robles et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…While SMYD1 is uniquely expressed in the heart and muscle, SMYD2 is expressed in multiple mammalian tissues including the kidney during development ( Jarrell et al, 2020 ). SMYD2 exerts its biological functions mainly through methylation of histone H3K36 and some non-histone proteins such as p53, phosphatase and tensin homolog deleted on chromosome 10 (PTEN), signal transducer and activator of transcription 3 (STAT3), and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) ( Yi et al, 2019 ; Weirich et al, 2020 ; Rueda-Robles et al, 2021 ). All of these non-histone proteins are involved in processes associated with the pathogenesis of AKI ( Holditch et al, 2019 ; Uber and Sutherland, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The MYND domain of SMYD2 is a zinc finger motif that facilitates the protein-protein interaction, while the SET domain, an evolutionarily conserved motif, catalyzes the transfer of methyl groups to lysine residues of target proteins using S-adenosylmethionine (SAM) as a donor substrate[ 12 ]. The carcinogenic potential of SMYD2 is exemplified by its ability to methylate a broad spectrum of proteins involved in cellular signaling, cell cycle control, and cell differentiation and proliferation[ 17 - 20 ]. SMYD2 is an epigenetic regulator that has histone lysine methyltransferase activity and can methylate histones H3K36 and H3K4[ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the tumor suppressor p53 is an important nonhistone target that is monomethylated by SMYD2 at Lys370 located in the regulatory domain of p53, repressing the p53’s transcriptional regulatory activity and promoting cancer initiation and growth[ 22 ]. It has also been shown that through its broad methyltransferase activity on nonhistone proteins, SMYD2 impacts various signaling pathways required for the development and progression of the malignancies[ 17 , 28 - 32 ]. These pathways include the critical signaling cascade RTK/Ras, the downstream signaling cascades of the RTK/Ras pathway, such as the mitogen-activated protein kinase (MAPK) pathway, and the PI3K/AKT pathway[ 16 , 27 , 28 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%